2012
DOI: 10.1111/j.1574-6968.2012.02598.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the flavonol morin on adhesion and aggregation of Streptococcus pyogenes

Abstract: The effect of the flavonol morin on Streptococcus pyogenes biofilm growth was determined using a static biofilm model, in which reduced biofilm biomass was observed in the presence of morin, suggesting that morin inhibited biofilm development. Morin at concentrations exceeding 225 μM had the greatest impact on biofilm biomass causing reductions of up to 65%, which was found to be statistically significant. Morin was also shown to induce rapid bacterial aggregation. Approximately 55% of S. pyogenes in liquid su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
(62 reference statements)
1
10
0
Order By: Relevance
“…The variation in the antibiofilm activity among various serotypes might be attributed to the varying amount of EPS layer present in each strain. Similarly to other reported biofilm inhibitors such as the flavanol morin (Green et al 2012) and manuka honey , usnic acid also showed a good reduction in biofilm biomass (Table 1). Bacterial aggregation plays a very important role in adherence to host receptors as well as other bacteria during biofilm development ).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The variation in the antibiofilm activity among various serotypes might be attributed to the varying amount of EPS layer present in each strain. Similarly to other reported biofilm inhibitors such as the flavanol morin (Green et al 2012) and manuka honey , usnic acid also showed a good reduction in biofilm biomass (Table 1). Bacterial aggregation plays a very important role in adherence to host receptors as well as other bacteria during biofilm development ).…”
Section: Discussionsupporting
confidence: 50%
“…The disturbing observation that one in three tonsillectomies can be colonized with GAS biofilms (Roberts et al 2012) in itself showcases the deleterious affects of GAS biofilms. Like other biofilms of pathogens, GAS biofilms also have been clinically related to antibiotic treatment failure (Baldassarri et al 2006) which has prompted several researchers to explore various natural resources such as medicinal plants (Limsuwan et al 2008;Samoilova et al 2014), plant derived flavanols (Green et al 2012), manuka honey , mangrove plants (Musthafa et al 2013), marine bacteria (Thenmozhi et al 2009;Nithyanand et al 2010) and phage encoded endolysins (Shen et al 2013) as antibiofilm agents against GAS biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…Morin hydrate (morin), a yellow natural bioflavonoid compound found in many members of the Moraceae family and various fruits and vegetables, has been shown to possess multiple pharmacological effects, including anti-inflammatory, anti-proliferative and anti-oxidant activities (Krol et al, 2002; Fang et al, 2005; Green et al, 2012; Lee et al, 2016). Additionally, several recent studies have shown that morin can significantly attenuate the virulence of pathogenic bacteria (Huang et al, 2014; Wang et al, 2015; Sivaranjani et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Among these, polyphenols, which are classified into flavonoids (e.g., catechin, flavonol, and tannin) and nonflavonoids (e.g., phenolic acid, neolignan), have been especially well studied [11, 12, 13, 14]. For example, it has been shown that tannins from tea leaves or persimmon have antibacterial effects against Streptococcus mutans , S .…”
Section: Introductionmentioning
confidence: 99%